2015 2nd International Conference on Recent Advances in Engineering &Amp; Computational Sciences (RAECS) 2015
DOI: 10.1109/raecs.2015.7453334
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of lubricating oil film pressure and temperarture of elliptical non-circular journal bearing profile

Abstract: The elliptical non-circular journal profile bearings provides more thermal stability than the circular journal bearings. The present study evaluates the thermal performance parameters such as oil film pressure and temperature experimentally along the circumference of an elliptical journal bearing. The tests have been conducted on the specially designed Journal Bearing Test Rig which is capable of measuring both pressure and temperature simultaneously at nine different locations along the central periphery of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As lubricants play a major role in hydrodynamic bearings, three different viscosity grades of mineral based lubricating oils 2,43 of Gulf make have been selected for examining the static performance of elliptical bearing. These oils, namely AW32, AW68 and AW100 have been labeled as LO1, LO2 and LO3, respectively for further discussion.…”
Section: Details Of Modeling Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…As lubricants play a major role in hydrodynamic bearings, three different viscosity grades of mineral based lubricating oils 2,43 of Gulf make have been selected for examining the static performance of elliptical bearing. These oils, namely AW32, AW68 and AW100 have been labeled as LO1, LO2 and LO3, respectively for further discussion.…”
Section: Details Of Modeling Parametersmentioning
confidence: 99%
“…Bearing is assumed with minor axis of 100.2 mm and major axis of 100.4 mm. Bearing dimensions have been chosen as per study done by Singla and Chauhan 43 for generating a model. The speed of the journal varies from 2000 to 5000 rpm with an interval of 1000 rpm.…”
Section: Details Of Modeling Parametersmentioning
confidence: 99%
“…It was observed that the bearing characteristics were greatly affected by the elastic deformation of the bearing surfaces. The effect of oil film temperature on the performance of elliptical journal bearing considering different loads and speeds was studied numerically by Chauhan et al [7] and experimentally by Singla and Chauhan [8] and [9]. The obtained results depict that the temperature and pressure at the mid plane of the bearing increased for higher journal speed and bearing eccentricity ratio while the oil film temperature decreases for the bearing with higher ellipticity factor.…”
Section: Introductionmentioning
confidence: 99%
“…15 Singla and Chauhan experimentally studied oil film pressure and temperature of an elliptical journal bearing, and they experimentally showed pressure and temperature profile with different load and speed. 16 Suryawanshi and Pattiwar studied the effect of blending TiO 2 nanoparticles with lubricating oil on the performance parameters of the elliptical journal bearing and plain bearing. They studied parameters such as pressure distribution, loadcarrying capacity, attitude angle, power loss, oil flow rate, side leakage, frictional force, and temperature rise in a film.…”
Section: Introductionmentioning
confidence: 99%